THE ANALYSIS OF LEXICOGRAMATICAL FEATURES AMONG ENGLISH SECOND LEARNER’S TEXTS - Imam Munandar (Asosiasi Dosen Perguruan Tinggi Islam, 2018)
This research has found that the pattern of ranks employed across the level of texts reveal a gradual development; from simple to complex. Namely, in the level of morphology, it shows that the texts develop from limited into varieduse of derivational and inflectional morphemes. This is in line with clause level of analysis in which we find its significant progress from simple clause to clause complex. Furthermore, the analysis of written language in term ofgrammatical function is one of Systematic Functional Grammar (SFG) contribution in language education. It can be a tool used by teachersand educators in assessingstudents’ language competences, especially in regard with students’ syntactic control over language. It can be expected to be an application of assessment that can provide a fundamental overview on how the assessed texts progress and develop. Meanwhile, another implication to language teaching is that it can provide an important view that teachers can rely on when deciding what level of topic leaningsthat suit their students.